2007
DOI: 10.1532/ijh97.07045
|View full text |Cite
|
Sign up to set email alerts
|

Living-Donor Lobar Lung Transplantation for Broncho-Bronchiolitis Obliterans after Allogeneic Hematopoietic Stem Cell Transplantation: Does Bronchiolitis Obliterans Recur in Transplanted Lungs?

Abstract: We report a successful case of living-donor lobar lung transplantation (LDLLT) for therapy-resistant broncho-bronchiolitis obliterans (BBO) after allogeneic hematopoietic stem cell transplantation (HSCT). Bronchiolitis obliterans (BO) is one of the late-onset noninfectious pulmonary complications that occur after allogeneic HSCT and is usually resistant to immunosuppressive therapy. A 17-year-old girl with acute lymphoblastic leukemia (ALL) had undergone allogeneic bone marrow transplantation (BMT) from an HLA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…3,13,14 The recipients of LDLLT following allo-HSCT from the same donor may require little or no immunosuppressive therapy. [13][14][15] It has been reported that the rate of PTLD, as a complication of LDLLT after allo-HSCT, was 10.5% in Japan. 13 The incidence of de novo malignancy after lung transplantation, including PTLD, appeared to be higher in patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…3,13,14 The recipients of LDLLT following allo-HSCT from the same donor may require little or no immunosuppressive therapy. [13][14][15] It has been reported that the rate of PTLD, as a complication of LDLLT after allo-HSCT, was 10.5% in Japan. 13 The incidence of de novo malignancy after lung transplantation, including PTLD, appeared to be higher in patients after allo-HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Even in Japan, it has recently been reported that lung transplantation for a patient with BO after allogeneic stem cell transplantation was successful. 16,17 However, it is difficult to find donors for lung transplantation because only a few are available and lung transplantation for cancer patients is not generally accepted in Japan. Therefore, living-donor lobar lung transplantation from family members might be the best choice for rescuing Japanese patients with BO accompanied by PNP.…”
Section: Discussionmentioning
confidence: 99%
“…However, successful cases of living-donor lobar lung transplantation (LDLLT) have been reported [155,156]. Given a severe deficit of cadaveric donor organs, LDLLT is performed for various lung diseases including BOS after HSCT in Japan [157].…”
Section: Therapy Of Bronchiolitis Obliterans Syndrome (Bos)mentioning
confidence: 99%